1980
DOI: 10.7326/0003-4819-92-2-202
|View full text |Cite
|
Sign up to set email alerts
|

Diverticular Disease in Patients with Chronic Renal Failure Due to Polycystic Kidney Disease

Abstract: Twelve patients with chronic renal failure and polycystic kidney disease represent 8% of the 151 hemodialysis patients followed up at the Chromalloy American Kidney Center, Washington University School of Medicine. Ten (83%) of these patients have diverticulosis, and four of these patients developed gross colonic perforation secondary to diverticulitis. Barium enemas on 31 chronic renal failure patients without polycystic kidney disease revealed diverticulosis in 10 (32%). None had diverticulitis. Barium enema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
11

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(74 citation statements)
references
References 10 publications
1
62
0
11
Order By: Relevance
“…This disorder is characterized by both renal and extra-renal manifestation (1,2). Colonic diverticulosis has been reported as a common manifestation of an extra-renal gastrointestinal tract complication (3). In addition, ileus has come to be recognized as one of the gastrointestinal complications of ADPKD (4).…”
Section: Introductionmentioning
confidence: 99%
“…This disorder is characterized by both renal and extra-renal manifestation (1,2). Colonic diverticulosis has been reported as a common manifestation of an extra-renal gastrointestinal tract complication (3). In addition, ileus has come to be recognized as one of the gastrointestinal complications of ADPKD (4).…”
Section: Introductionmentioning
confidence: 99%
“…CoffinLowry syndrome is a maternally inheritable disorder that may also be related to disrupted collagen metabolism [88] . Scheff et al [91] observed colonic diverticulae in 83% of patients with end stage polycystic kidney disease (PKD). PKD is due to mutations in the PKD1 or PKD2 genes coding for the cell membrane-bound polycystin proteins.…”
Section: The Role Of Genetics In Ddmentioning
confidence: 99%
“…[9][10][11][12][13] Various studies reported that the prevalence of colonic diverticulosis is significantly higher in patients with autosomal dominant polycystic kidney disease (ADPKD) than in the general population or patients on dialysis for other renal diseases. 4,[14][15][16][17][18] Prevalence rates vary from 53.5% to 83%, with the condition attributed to a congenital colonic defect or the secretory action from the renal cysts on the colonic wall. 8 However, the extent of colonic diverticulitis and perforation does not seem to correlate with the primary renal disease.…”
Section: Discussionmentioning
confidence: 99%